What Is Stopping the Renewable Energy Transformation and What Can the US Government Do? - Cohen, Steven (Social Research)
The article identifies the hindrances, including the evolution of technology, to the implementation of a policy gearing towards the transition to a renewable energy environment in the U.S. as of September 2015. The barriers including advancing technology, infrastructure, and complex political nature are being scrutinized for a renewable resource-based economy. The role of the public sector in the transition to a sustainable global economy is acknowledged. According to the U.S. Department of Energy's National Renewable Energy Laboratory, combination of renewable electricity generation and a flexible electric system can sufficiently supply huge percentage of total electricity generation.